Net rainfall components under various ages of the oil palm - Farmanta, Y.; Sung, C. T. B.; Giap, S. E. G; Paing, T. N.; Handoko; Impron (Malaysian Society of Soil Science, 2021)
This study analysed the net rainfall components under different ages and leaf area index (LAI) of the oil palm to determine the contribution of net rainfall towards water requirements of the palm. We hypothesised that older palms, with their higher LAI, would have lower net rainfall due to higher interception of rain. The study was conducted in oil palm plantations in Mendis village, Bayung Lincir District, Sumatra. Tipping-bucket rain gauges connected to data loggers were used to measure the rainfall components (throughfall, stemflow, interception and gross rainfall) at ten-minute intervals for four months. The proportions of throughfall, stemflow, and interception for the oil palm aged between 5 to 20 years were 92.2% - 58%, 2.4 – 0.7%, and 5.4% - 41%, respectively. The equations relating throughfall (Tf), stemflow (Sf), and net rainfall (Pn) to LAI were Tf = -8.5032 LAI + 116.74, Sf = -0.469 LAI + 3.8808, and Pn = -8.9722 LAI + 120.62, respectively. Under various oil palm ages, net rainfall (Pn) had an inverse linear relationship with an increase in LAI by 3.5 and 7.2 with a decrease in net rainfall from 94.6% to 58.8%. The results from this study should serve as a guide to the water management of oil palm plantations.